EFFECTS OF ANIMATION-BASED CAMSTUDIO PHYSICS INSTRUCTION ON SECONDARY SCHOOL STUDENTS’ PERFORMANCE IN MINNA, NIGERIA - M. V., Adegbija; C.O., Falode (European Scientific Journal, ESJ, 2014)
This study was carried out to determine the effect of Animationbased CamStudio Physics Instructional Package (ACPIP) on secondary school physics students’ performance in Minna, Nigeria. Two research hypotheses were formulated and tested at 0.05 level of significance. Purposive sampling technique was employed in selecting two co-educational secondary schools in Minna, metropolis from where eighty (80) senior secondary school two (SS II) Physics students were sampled for the study. Students in the experimental group ((20boys & 20girls)) were taught physics using ACPIP while their counterparts in the control group ((20boys & 20girls)) were taught using the conventional lecture method. Animationbased CamStudio Physics Instructional Package (ACPIP) which contains three secondary school Physics concepts in Waves and the Physics Achievement Test (PAT) were the two research instruments used for the study. The PAT comprises 30-item multiple-choice Physics questions. The Kudar-Richardson (KR=21) formula used to determine the reliability coefficient of PAT yielded 0.89, while mean and t-test statistics were used to test the two hypotheses in SPSS 16.0. Findings revealed that students taught Physics using Animation-based CamStudio Instructional Package performed significantly better than those taught using conventional lecture method (tcal= 6.043, df = 78, p = 0.000), but there was no significant difference between the mean achievement scores of male and female students taught Physics using ACPIP (tcal= 0.604, df = 38, p = 0.550). Based on the findings, it was recommended that Animation-based physics instruction should be used to supplement conventional classroom instruction and for revision purposes in order to improve students’ performance in physics.